2019
DOI: 10.2147/ijn.s210035
|View full text |Cite
|
Sign up to set email alerts
|

<p>Would Colloidal Gold Nanocarriers Present An Effective Diagnosis Or Treatment For Ischemic Stroke?</p>

Abstract: IntroductionThis study was conducted to evaluate OX26-PEG-coated gold nanoparticles (GNPs) (OX26@GNPs) as a novel targeted nanoparticulate system on cell survival after ischemic stroke.Materials and methodsDynamic light scattering (DLS), zeta sizer, and transmission electron microscopy (TEM) were performed to characterize the OX26@GNPs. The effect of OX26@GNPs on infarct volume, neuronal loss, and necroptosis was evaluated 24 h after reperfusion using 2, 3,5-Triphenyltetrazolium chloride (TTC) staining, Nissl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 58 publications
0
68
0
Order By: Relevance
“…36 Amani et al showed that surface charge played an important role in cell survival. 37 Li et al reported enhanced bioactivity on the TiO 2 surface with more negative zeta potential. 38 Referring to the zeta potential of the different modified Ti surfaces reported in the above articles in conjunction with the results of the present study, we found that the lower the zeta potential of the surface, the stronger the osseointegration ability.…”
Section: Discussionmentioning
confidence: 99%
“…36 Amani et al showed that surface charge played an important role in cell survival. 37 Li et al reported enhanced bioactivity on the TiO 2 surface with more negative zeta potential. 38 Referring to the zeta potential of the different modified Ti surfaces reported in the above articles in conjunction with the results of the present study, we found that the lower the zeta potential of the surface, the stronger the osseointegration ability.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombolytic therapy using tissue plasminogen activator (t-PA) is known as a promising treatment for ischemic stroke. However, t-PA has narrow therapeutic time window because of its severe hemorrhagic side effects that induce inflammation of brain capillaries and subsequently severe injury to neurons after stroke (Amani et al, 2019b). Therefore, the use of t-PA is restricted to selected patients only, and patients who have not been treated with t-PA will suffer from serious aftereffects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the blood-brain barrier, consisting of endothelial cells, tight junctions, astrocytic end-feet processes, pericytes, and basement membrane, is essential in regulation of the passage of inflammatory cytokines, proteins, and ions between the brain and plasma [23]. Studies have shown that disruption of the blood-brain barrier in ischemic stroke could increase the permeability and change the microenvironment of the brain, which may contribute to the further development of brain damage [5][6][7][8][9][10][11][12]24]. Zhang et al demonstrated that a novel IL-1RA-PEP fusion protein could effectively improve cerebral I/R injury by inhibiting the blood-brain barrier permeability [25].…”
Section: Discussionmentioning
confidence: 99%